2020
DOI: 10.17305/bjbms.2020.5181
|View full text |Cite
|
Sign up to set email alerts
|

MPTP-induced mouse model of Parkinson’s disease: A promising direction of therapeutic strategies

Abstract: Amongst the popular animal models of Parkinson’s disease (PD) commonly used in researches are those that employ neurotoxins, especially the 1-methyl- 4-phenyl-1, 2, 3, 6-tetrahydropyridine (MPTP). MPTP neurotoxin exerts its neurotoxicity by causing a barrage of insults such as oxidative stress, mitochondrial apoptosis, inflammation, excitotoxicity, and formation of inclusion bodies acting singly and in concert. All of this ultimately leads to dopaminergic neuron damage in substantia nigra pars compacta and str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(40 citation statements)
references
References 91 publications
(155 reference statements)
0
40
0
Order By: Relevance
“…Mitochondrial dysfunction is a major hallmark of neurodegenerative disease, including synucleinopathies, such as MSA, PD, PDD, and DLB. Over the past 47 years, human and animal studies have shown that the mitochondrial toxin 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP), a mitochondrial complex I inhibitor, induces parkinsonian-like symptoms associated with the loss of DA neurons (Langston et al, 1983;Kopin and Markey, 1988;Kopin, 1992;Langston, 2017;Mat Taib and Mustapha, 2020). Such studies have cemented the link between mitochondrial dysfunction and PD.…”
Section: Pd Chchd2 and α-Synuclein Pathologymentioning
confidence: 99%
“…Mitochondrial dysfunction is a major hallmark of neurodegenerative disease, including synucleinopathies, such as MSA, PD, PDD, and DLB. Over the past 47 years, human and animal studies have shown that the mitochondrial toxin 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP), a mitochondrial complex I inhibitor, induces parkinsonian-like symptoms associated with the loss of DA neurons (Langston et al, 1983;Kopin and Markey, 1988;Kopin, 1992;Langston, 2017;Mat Taib and Mustapha, 2020). Such studies have cemented the link between mitochondrial dysfunction and PD.…”
Section: Pd Chchd2 and α-Synuclein Pathologymentioning
confidence: 99%
“…The neurotoxin1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP), was initially recognized to be related to nigrostriatal degeneration, following the emergence of characteristic manifestations of PD in several individuals upon self-administration of narcotic substances contaminated with MPTP. MPTP is bio transformed into an active toxic metabolite named 1-methyl-4-phenylpyridinium ion (MPP+), which belongs to the family of mitochondrial complex-I suppressors, and is exclusively involved in devastating DArgic nerve cells within the SN [ 106 , 107 ]. The exploration of MPTP as a triggering factor for degeneration within the SN encouraged the postulation that PD might be precipitated by toxic substances present in the environment [ 108 ].…”
Section: Etiology Of Pdmentioning
confidence: 99%
“…Based on the aforementioned findings, we speculate that controversial experimental results were obtained because of the limited pathogenesis of ND mouse models. Human ND etiologies are quite intricate, involving long-term manifold metabolic disorders, gut microbiota alteration, gene mutation, and various hereditary factors, whereas most mouse model etiologies rely on gene editing or medical injection, which might lead to inconsistent pathogenic processes ( 24 , 193 201 ). Third, studies have demonstrated that microbiota altered with aging; yet, no evidence is available to confirm whether the altered microflora is healthy, unhealthy, stable, or vulnerable ( 10 , 15 , 22 , 113 , 202 ).…”
Section: Controversies and Perspectivesmentioning
confidence: 99%